2023
DOI: 10.24875/gmm.m18000125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of 200 patients with recurrent aphthous stomatitis

Abstract: Introduction: Recurrent aphthous stomatitis (RAS) affects approximately 20% of the general population. Its etiology is still unknown. Objective: To analyze this entity's clinical features. Method: Data such as age, gender, family history of RAS, age at first episode onset, prodromal symptoms, number, size, morphology and localization of lesions, RAS clinical form, annual rate of recurrence, predisposing factors, symptoms and time for symptoms and lesions disappearance were assessed in 200 patients with RAS. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(94 reference statements)
0
3
1
1
Order By: Relevance
“…21 These findings are similar to a study conducted by Rathod et al, which concluded that the ulcers healed within 2 to 5 days in most patients (96.36%). 19 Meanwhile, this study is slightly different from the study by Hedge et al 18 and Rodriguez-Archilla et al 22 Hedge et al recorded that ulcers healed in less than 1 week in 46.2% of patients, in 1 to 2 weeks in 38% of patients, and in more than 2 weeks in 15.8% of patients. 18 In the study by Rodriguez-Archilla et al comprising 200 individuals with recurrent aphthous stomatitis, 49% of lesions healed in less than 7 days and 51% in more than 7 days.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…21 These findings are similar to a study conducted by Rathod et al, which concluded that the ulcers healed within 2 to 5 days in most patients (96.36%). 19 Meanwhile, this study is slightly different from the study by Hedge et al 18 and Rodriguez-Archilla et al 22 Hedge et al recorded that ulcers healed in less than 1 week in 46.2% of patients, in 1 to 2 weeks in 38% of patients, and in more than 2 weeks in 15.8% of patients. 18 In the study by Rodriguez-Archilla et al comprising 200 individuals with recurrent aphthous stomatitis, 49% of lesions healed in less than 7 days and 51% in more than 7 days.…”
Section: Discussioncontrasting
confidence: 52%
“…18 In the study by Rodriguez-Archilla et al comprising 200 individuals with recurrent aphthous stomatitis, 49% of lesions healed in less than 7 days and 51% in more than 7 days. 22 The duration required for healing of the ulcer depends on the type of ulcer. The process of oral ulcer healing involves four phases: hemostasis, inflammation, proliferation, and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent aphthous stomatitis (RAS) is the commonly found oral lesion in the community, with nearly 10-30% of the population are affected. 17,18,19,20 Evidently, RAS was found in 55% among all the oral ulceration cases (Figure 3). Following RAS, traumatic ulcer (TU) came next with 43% from the oral ulcerative diagnosis, and angular cheilitis (AC) came third with 2% ( Figure 3).…”
Section: Discussionmentioning
confidence: 90%
“…1 This is also supported by Rodríguez-Archilla and Raissouni, whose statistical analysis shows that RAS is more common in females than males. 14 In addition, the study conducted by Sulistiani et al also states that RAS is more common in females than males, with approximately 70.0% of RAS patients being female. 15 The same was also revealed in Abdullah's research, which found that the majority of RAS patients were female (55.4%).…”
Section: Discussionmentioning
confidence: 98%